The Pain of Philosophy: A Cynic Objection to Plato - Nagao, Masaki (Peitho. Examina Antiqua, 2025)
According to the apophthegm reported by Plutarch and Stobaeus (SSR V B 61), Diogenes the Cynic accused Plato of ‘causing pain to no one’ during his long philosophical career. This article considers whether this critique of Plato is accurate by examining previous interpretations and proposing others. First, Plutarch understood the ‘pain’ required by Diogenes as a psychological motivator that drives the young to study hard. This interpretation, however, is implausible because Plato does not seem unfamiliar with this treatment of ‘pain’. Second, Stobaeus connected pain with parrhēsia, likely supposing that a philosopher should tell the truth even if it hurts his audience. Nevertheless, his account needs further clarification since Plato also emphasises the importance of parrhēsia. To resolve the problem, this article proposes a distinction between two kinds of parrhēsia: ‘telling the truth’ and ‘openly making abusive remarks’. Unlike Plato, the Cynics occasionally resort to the latter, which causes sufferers completely passive pain. This kind of pain is certainly alien to Plato’s philosophy, which presupposes some active participation by sufferers. Finally, the article introduces the Cynic concept of askēsis to illuminate another aspect of ‘philosophical pain’. While Plato confines his askēsis to mental labour or moderate physical exercise, the Cynics also demand that individuals undergo physical pain in the course of askēsis. In conclusion, the article argues that Diogenes’ objection to Plato is apt, at least in light of two antithetical natures of ‘pain’: passive/active and physical/mental.